Interdependence of approach and avoidance goals in romantic couples over days and months - Nikitin, Jana; Wünsche, Jenna; Bühler, Janina Larissa; Weidmann, Rebekka; Burriss, Robert P.; Grob, Alexander (The journals of gerontology. Series B, Psychological sciences, social sciences, 2021)
AbstractObjectives. Despite the centrality of people’s approach goals (i.e., approach toward positive outcomes) and avoidance goals (i.e., avoidance of negative
Advance access publication: September 3, 2020
Gesehen am 01.12.2021